Incidence and short outcome in multiple pregnancies: a single center cross-sectional study in Iran 2016–2017 (Faculty of Medicine Universitas Indonesia, 2019)
BACKGROUND The incidence of multiple pregnancies in industrialized countries due to the use of assisted reproductive techniques has increased over the past two decades. Multiple births are more dangerous than single pregnancies for mother and baby. This study evaluated the frequency of multiple pregnancies and its neonatal complications. METHODS In this cross-sectional study, we assessed all multiple neonates hospitalized in Fatemieh Hospital of Hamadan, Iran from September 2016 to September 2017 in terms of gender, gestational age, birth weight, the use of assisted reproductive techniques, delivery method, cause of hospitalization, therapeutic intervention, and hospitalization outcome. RESULTS Of 10,581 deliveries during the study period, 351 (3.3%) was multiple pregnancies and 232 neonates hospitalized. The incidence of twin, triplet, and quadruplet birth were 1.7%, 0.39%, and 0.11% respectively. In this study, 178 twin and 54 triplet and quadruplet birth were compared. The mean gestational age and mean birth weight of triplet and quadruplet were lower than that of twin births (p<0.001). A significant difference was found on the frequency of assisted reproductive techniques (p<0.001). Female sex (p=0.007), lower mean gestational age (p=0.009), lower mean birth weight (p=0.017) and need to mechanical ventilation (p<0.001) were significantly associated with early neonatal death in multiple pregnancies. CONCLUSIONS The incidence of multiple births was high in the Hamadan province, which was often followed by infertility treatment. Moreover, multiple births cause prematurity, low birth weight, respiratory distress syndrome, and increased neonatal mortality rate.